Organizational Culture and its Role in Promoting the Enterpreneurial Orientation toBusiness Organizations: an Exploratory Search of the views of a sample of Asia Cell Telecommunications Company Managers in Karbala/ Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The current research aims to indicate the role of Organizational Culture in Entreprenerurial Orientation in the Asia Cell Telecommunications Company in Karbala/ Iraq, and to achieve this goal has been the adoption of a questionnaire composed of two axes, the first to include data relating to the respondent for form, and the second research variables. Have been distributed (20) questionnaire on the company surveyed managers (sample) The response rate (100%), and based on some statistical methods such as arithmetic mean, standard deviation, central premise to test the validity of the hypothesis search, and in the light of the results, the search to some of the recommendations including the consolidation of organizational culture an integral part of the company and make it researched trends.